3x-(4x+8)=2(16-x)

Simple and best practice solution for 3x-(4x+8)=2(16-x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-(4x+8)=2(16-x) equation:


Simplifying
3x + -1(4x + 8) = 2(16 + -1x)

Reorder the terms:
3x + -1(8 + 4x) = 2(16 + -1x)
3x + (8 * -1 + 4x * -1) = 2(16 + -1x)
3x + (-8 + -4x) = 2(16 + -1x)

Reorder the terms:
-8 + 3x + -4x = 2(16 + -1x)

Combine like terms: 3x + -4x = -1x
-8 + -1x = 2(16 + -1x)
-8 + -1x = (16 * 2 + -1x * 2)
-8 + -1x = (32 + -2x)

Solving
-8 + -1x = 32 + -2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2x' to each side of the equation.
-8 + -1x + 2x = 32 + -2x + 2x

Combine like terms: -1x + 2x = 1x
-8 + 1x = 32 + -2x + 2x

Combine like terms: -2x + 2x = 0
-8 + 1x = 32 + 0
-8 + 1x = 32

Add '8' to each side of the equation.
-8 + 8 + 1x = 32 + 8

Combine like terms: -8 + 8 = 0
0 + 1x = 32 + 8
1x = 32 + 8

Combine like terms: 32 + 8 = 40
1x = 40

Divide each side by '1'.
x = 40

Simplifying
x = 40

See similar equations:

| P+5p=-12 | | 5x-21=19 | | 2.625(x/8+0.125)=64 | | 4x^2-19x+31=4x+3 | | 14x-8+2x-5=13x-3+2x | | 6(x+2)-(x-3)=3(-x+1) | | X-6=2x-15 | | 4(1-5x)-4=10x | | (2a^3b^3+7ab^2)+(5ab^2-2a^3b^3)= | | 8x+5x=104 | | 7x-2x+9+3x+8-5x+6=5 | | x-3(x-12)=26 | | 5(3x+2)=32.5 | | (x-3)(15-6x)=0 | | 17=2x+8 | | x(2x-5)=8 | | 15x-40+21x+18=48x+18-8x-20 | | ax+2=3x+a | | 4x+4=4y | | 12w^4+56w^3+32w^2=0 | | x^4=-25 | | 5x+13=42 | | 4y+10=46 | | 4u^3w^4+12u^9w^6x^9=0 | | 8.7+3.6-5.3= | | 12-10x=80-38x | | 3(4x+5)(3x-2)=0 | | 6(n+4)=8+7n | | 18d-4d-6d-8=2d | | -5m=4m+8 | | 7(m-3)=4(m+3) | | (2x-6)m=26 |

Equations solver categories